CD74 promotes the formation of an immunosuppressive tumor microenvironment in triple-negative breast cancer in mice by inducing the expansion of tolerogenic dendritic cells and regulatory B cells. - Bianca Pellegrino; Keren David; Stav Rabani; Bar Lampert; Thuy Tran; Edward Doherty; Marta Piecychna; Roberto Meza-Romero; Lin Leng; Dov Hershkovitz; Arthur A Vandenbark; Richard Bucala; et al. (PLoS Biology, 2024)
CD74 is a cell-surface receptor for the cytokine macrophage migration inhibitory factor (MIF). MIF binding to CD74 induces a signaling cascade resulting in the release of its cytosolic intracellular domain (CD74-ICD), which regulates transcription in naïve B and chronic lymphocytic leukemia (CLL) cells. In the current study, we investigated the role of CD74 in the regulation of the immunosuppressive tumor microenvironment (TME) in triple-negative breast cancer (TNBC). TNBC is the most aggressive breast cancer subtype and is characterized by massive infiltration of immune cells to the tumor microenvironment, making this tumor a good candidate for immunotherapy. The tumor and immune cells in TNBC express high levels of CD74; however, the function of this receptor in the tumor environment has not been extensively characterized. Regulatory B cells (Bregs) and tolerogenic dendritic cells (tol-DCs) were previously shown to attenuate the antitumor immune response in TNBC. Here, we demonstrate that CD74 enhances tumor growth by inducing the expansion of tumor-infiltrating tol-DCs and Bregs. Utilizing CD74-KO mice, Cre-flox mice lacking CD74 in CD23+ mature B cells, mice lacking CD74 in the CD11c+ population, and a CD74 inhibitor (DRQ), we elucidate the mechanism by which CD74 inhibits antitumor immunity. MIF secreted from the tumor cells activates CD74 expressed on DCs. This activation induces the binding of CD74-ICD to the SP1 promotor, resulting in the up-regulation of SP1 expression. SP1 binds the IL-1β promotor, leading to the down-regulation of its transcription. The reduced levels of IL-1β lead to decreased antitumor activity by allowing expansion of the tol-DC, which induces the expansion of the Breg population, supporting the cross-talk between these 2 populations. Taken together, these results suggest that CD74+ CD11c+ DCs are the dominant cell type involved in the regulation of TNBC progression. These findings indicate that CD74 might serve as a novel therapeutic target in TNBC.